Essential Oils- A Natural Alternative for Storage Pest Management - Keerthana, B.; Chowdappa, A.; Padmasri, A.; Snehalatha, G. (Chronicle of Bioresource Management, 2025)
Ensuring food security is a growing challenge, especially with increasing post-harvest losses caused by storage pests and fungi. Conventional pest management methods, including synthetic insecticides and fungicides, pose risks such as pesticide resistance, environmental contamination, and health hazards. Essential oils derived from plants and their components offer a promising alternative for storage pest and fungi management due to their insecticidal and antifungal properties. However, their efficacy is often limited by volatility, oxidation, and water solubility. To combat these challenges, advanced formulations such as nanocomposites and bio-composites can enhance stability, prolong their shelf life through slow and controlled release while maintaining mammalian safety.